Urban Planning In Ibadan, Nigeria 1960 to 2010: A Historical Analytical Study with Special Reference to Islamic Connections - Abiola, Ibraheem Mikail; Ibrahim, Hassan Ahmed (Asian Journal of Social Sciences and Management Studies, 2015)
Ibadan is located in Southwestern Nigeria, in the southeastern part of Oyo state about 120km east of the border to Republic of Benin. The city’s total area is 1,190 sq miles (3,080km2). The city isnaturally drained by four rivers which have many tributaries: Ona River in the north and west, Ogbere River towards the east, Ogunpa flowing through the city and Kudeti River in the centralpart of Ibadan metropolis. Ogunpa River the third stream has a channel length of 12.76km and a catchment area of 54.92km2.